2004
DOI: 10.1007/s00239-004-2587-x
|View full text |Cite
|
Sign up to set email alerts
|

The Decline of Isochores in Mammals: An Assessment of the GC ContentVariation Along the Mammalian Phylogeny

Abstract: Abstract. Whether isochores, the large-scale variation of the GC content in mammalian genomes, are being maintained has recently been questioned. It has been suggested that GC-rich isochores originated in the ancestral amniote genome but that whatever force gave rise to them is no longer effective and that isochores are now disappearing from mammalian genomes. Here we investigated the evolution of the GC content of 41 coding genes in 6 to 66 species of mammals by estimating the ancestral GC content using a met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
63
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 31 publications
6
63
1
Order By: Relevance
“…The erosion of GC-rich isochores in primates was again confirmed by the analysis of substitutions in introns and intergenic regions (Webster et al 2003;Meunier and Duret 2004). This erosion of GC-rich isochores has also been noted in carnivores, but not in lagomorphs or perissodactyls (Belle et al 2004). …”
mentioning
confidence: 57%
See 1 more Smart Citation
“…The erosion of GC-rich isochores in primates was again confirmed by the analysis of substitutions in introns and intergenic regions (Webster et al 2003;Meunier and Duret 2004). This erosion of GC-rich isochores has also been noted in carnivores, but not in lagomorphs or perissodactyls (Belle et al 2004). …”
mentioning
confidence: 57%
“…The latter result was criticized because the cetartiodactyls species that we had analyzed were too distantly related and, therefore, the parsimony approach that we had used was not reliable (Alvarez-Valin et al 2004). Indeed, the analysis of synonymous substitutions by a maximum likelihood approach confirmed the erosion of GC-rich isochores in primates and in rodents, but not in cetartiodactyles (Belle et al 2004). The erosion of GC-rich isochores in primates was again confirmed by the analysis of substitutions in introns and intergenic regions (Webster et al 2003;Meunier and Duret 2004).…”
mentioning
confidence: 95%
“…The isochore structure is vanishing in mammalian genomes, according to recent studies (Duret et al 2002;Arndt et al 2003b;Belle et al 2004). Moreover, Meunier and Duret (2004) have demonstrated that the current substitution pattern in human genome should lead to a new isochore structure, with a lower GC mean and a lower variance.…”
Section: Evolution Of Isochore Structure In Mammalian Genomesmentioning
confidence: 95%
“…Kauppi and colleagues (2004) have demonstrated that the rate of gene conversion outside CO is 4 to 15 times higher than the rate of gene conversion inside CO. Recent works have demonstrated that GC-BGC can increase GC content very quickly (Belle et al 2004;Kudla et al 2003;Galtier 2004;Webster et al 2005). The rate of gene conversion is 100 times higher than the rate of neutral substitutions in mammalian genomes (Kudla et al 2004), which could be enough to induce a tremendous change in GC content and in isochore structure.…”
Section: The Impact Of Recombination On Gc Content Evolutionmentioning
confidence: 99%
“…S6). The wider distribution of GþC content in human and dog is thus likely to reflect the boreoeutherian ancestor 44,45 , with the more homogeneous composition in rodents having arisen primarily through lineagespecific changes in substitution patterns 46,47 rather than deletion of sequences with high GþC content. Rate of nucleotide divergence.…”
Section: Generating a Draft Genome Sequencementioning
confidence: 99%